Election Smart House (ESH) as a Pre-Voter Political Education Facility To improve the quality of democracy - Hariyanti Hariyanti; Filma Alia Sari (Universitas of Muhammadiyah Makassar, 2021)
Abstract. This study aims to describe the Election Smart House (RPP) as a means of pre-voting political education in Pekanbaru City and Dumai City. The study uses a qualitative approach with descriptive methods. Determination of research informants through non-probability sampling techniques with purposive sampling techniques. The data validity testing technique uses triangulation of data sources. The research findings show that pre-voting political education through the use of lesson plans is carried out in two ways, namely (1) a program to disseminate lesson plans to schools. The Election Commission of Pekanbaru City conducted socialization of lesson plans to kindergartens and elementary schools, while junior and senior high schools had not yet done so because of time constraints. While the General Election Commission of Dumai City has never carried out socialization of the RPP to schools, but rather it was carried out in tertiary institutions and; (2) hearings (visits) to the lesson plan. Pre-voter hearing activities have never been conducted in the Pekanbaru City RPP, while the Dumai City RPP has received a one-time visit from the school, namely the Erna City Vocational School in Dumai in December 2019. The RPP as a means of pre-voting political education has not run optimally. This is indicated by the lack of socialization of the RPP to the pre-voters and pre-voter visits to the RPP. In addition, the General Election Commission as the manager of the RPP does not have a special / routine program in educating pre-voters through the use of the RPP. Some efforts are needed to increase the political literacy of pre-voters through the use of RPPs such as the special RPP program that is carried out periodically through the collaboration of the General Election Commission as the manager of RPPs and schools through PPKn teachers as subjects integrated with electoral and pre-voter visits to RPPs.Keywords: Election Smart House, Political Education, Pre-election, DemocracyAbstrak. Penelitian ini bertujuan untuk mendeskripsikan Rumah Pintar Pemilu (RPP) sebagai sarana pendidikan politik prapemilih di Kota Pekanbaru dan Kota Dumai. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Penentuan informan penelitian melalui teknik non probability sampling dengan teknik purposive sampling. Teknik pengujian keabsahan data menggunakan triangulasi sumber data. Temuan penelitian menunjukkan bahwa pendidikan politik prapemilih melalui pemanfaatan RPP dilakukan melalui dua cara yakni (1) program kegiatan sosialisasi RPP ke sekolah. Komisi Pemilihan Umum Kota Pekanbaru melakukan sosialisasi RPP ke taman kanak-kanak dan sekolah dasar, sedangkan untuk jenjang SMP dan SMA belum dilakukan karena terkendala waktu. Sementara Komisi Pemilihan Umum Kota Dumai belum pernah melakukan sosialisasi RPP ke sekolah, melainkan dilaksanakan di perguruan tinggi dan; (2) audiensi (kunjungan) ke RPP. Kegiatan audiensi prapemilih belum pernah dilakukan di RPP Kota Pekanbaru, sedangkan RPP Kota Dumai pernah menerima kunjungan sekali dari sekolah yakni SMK Erna Kota Dumai pada Desember 2019. RPP sebagai sarana pendidikan politik prapemilih belum berjalan secara optimal. Hal tersebut ditunjukkan dengan minimnya sosialisasi RPP kepada prapemilih maupun kunjungan prapemilih ke RPP. Selain itu, Komisi Pemilihan Umum sebagai pengelola RPP tidak mempunyai program khusus/rutin dalam mengedukasi prapemilih melalui pemanfaatan RPP. Diperlukan beberapa upaya untuk meningkatkan literasi politik prapemilih melalui pemanfaatan RPP seperti adanya program khusus RPP yang dilaksanakan secara berkala melalui kerjasama Komisi Pemilihan Umum sebagai pengelola RPP dan sekolah melalui guru PPKn sebagai mata pelajaran yang terintegrasi dengan kepemiluan serta kunjungan prapemilih ke RPP.Kata Kunci: Rumah Pintar Pemilu, Pendidikan Politik, Prapemilih, Demokrasi.